Determination of Alkaloids Constituents in Some Ferns by Using High Performance Liquid Chromatography Technique – Iraq - Alallaq, Sanaria A.; Murtadeh, Ismail A.; Al-Majmaie, S. Hatem (Iraqi Journal of Science, 2023)
Ferns are considered as important medical herbs. They produce a wide range of secondary metabolites that could be useful in treating different diseases. However, they still remain underexplored in medical aspects in Iraq. Hence, the purpose of this study was to identify alkaloids components in the methanol extracts of four fern species (Asplenium ceterach L., A. scolopendrium L., Cheilanthes pteridioides (Richard) C. Chr. from Malakan region in Erbil Governorate and Equisetum ramosissimum Desf. from Chemi Rezan in Sulaimaniyah Governorate,  of northen Iraq during March - June 2018. The research was conducted by using High performance liquid chromatography (HPLC) technique to identify the alkaloid compounds. Seven types of alkaloids (martensine, almazoline, caulerpin, hordenine, corilagin, colocynthis and isoquinoline) were detected in four fern methanolic extracts. The results showed that the alkaloids varied in concentrations between the studied localities as well as in variance of the alkaloid content between these species. The results revealed that caulerpin was recorded as the highest concentration (563.3 µg/ ml), while isoquinoline was recorded as the lowest (23.7 µg/ ml) in both A. scolopendrium and C. pteridioides. In this study the highest total alkaloid content was recorded 1460.1 µg/ ml in E. ramosissimum extract and the lowest content (603.8 µg/ ml) was recorded in C. pteridioides extract during the study period.